CHARACTERISTICS PROTECTION OF MADURA TOBACCO THROUGH THE GEOGRAPHICAL INDICATIONS REGIME - Djulaeka Djulaeka; Makhmud Zulkifli (Jurnal Dinamika Hukum, 2015)
Madura Tobacco has typical characteristics which are grow in the area of Madura, especially in Pamekasan and Sumenep area. The different specificity of the Madura tobacco with tobacco in other regions makes tobacco has the potential to get the protection of geographical indications as one of the intellectual property rights regime. Issues of the research focused on the importance of geographical indications for typical regional products, local institutional role in protecting regional superior products and local institutional constraints that exist in Pamekasan and Sumenep area as legal standing in an effort to protect the tobacco through the regime of geographical indications.This study is an empirical research with qualitative approach and research located in Madura, especially in Pamekasan and Sumenep area. The results showed that geographical indications can provide local products a protection, local agencies in the area of research references tend to be dormant and do not understand the potential protection of geographical indications for tobacco. Political will of the Local Government is the key word in the protection of geographical indications based on regional products. Key Words: geographical indications, legal standing, madura tobacco.